YOUTH UNEMPLOYMENT AND THE ROLE OF TOURISM SMES AS AN INCLUSIVE EMPLOYMENT GENERATOR IN UZBEKISTAN (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2026)
Despite Uzbekistan's declining overall unemployment rate, youth unemployment remains structurally elevated, reflecting a mismatch between education and labor market needs. This article examines whether tourism small and mediumsized enterprises (SMEs) can serve as an inclusive employment generator for youth. Drawing on official statistics and recent IMF and World Bank data, the study finds that tourism SMEs offer structural advantages - low capital thresholds, labor intensity, and geographic reach into rural areas - that favor inclusive youth employment, though skills mismatches, seasonality, and financing constraints limit this potential. The article concludes with recommendations on vocational training, preferential financing, and infrastructure investment in secondary tourism destinations.
Keywords: youth unemployment; tourism SMEs; inclusive employment; entrepreneurship; Uzbekistan; labor market policy